2003
DOI: 10.1093/jn/133.7.2171
|View full text |Cite
|
Sign up to set email alerts
|

Garlic (Allium sativum L.) Modulates Cytokine Expression in Lipopolysaccharide-Activated Human Blood Thereby Inhibiting NF-κB Activity

Abstract: Garlic is proposed to have immunomodulatory and anti-inflammatory properties. This paper shows that garlic powder extracts (GPE) and single garlic metabolites modulate lipopolysaccharide (LPS)-induced cytokine levels in human whole blood. GPE-altered cytokine levels in human blood sample supernatants reduced nuclear factor (NF)-kappaB activity in human cells exposed to these samples. Pretreatment with GPE (100 mg/L) reduced LPS-induced production of proinflammatory cytokines interleukin (IL)-1beta from 15.7 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 21 publications
1
98
0
Order By: Relevance
“…11 Garlic contains diverse organosulfur compounds such as S-allyl-l-cysteine, diallyl disulfide, diallyl trisulfide, ajoene, and allicin, which have potent antioxidative, antibacterial, antiviral, and anticancer properties. [11][12][13] The major watersoluble sulfur compound, S-allyl-l-cysteine, in garlic extract seems to have direct inhibitory effect on nuclear factor-jB (NF-jB) and indirect inhibitory effect on lipopolysaccharide (LPS)-induced IL-1b and TNF-a in human whole blood. 14,15 The lipid-soluble sulfur compounds allicin and diallyl disulfide also inhibit NF-jB and reduce the expression of inducible nitric oxide (NO) synthase (iNOS) in LPS-stimulated macrophages.…”
Section: Introduction Gmentioning
confidence: 99%
“…11 Garlic contains diverse organosulfur compounds such as S-allyl-l-cysteine, diallyl disulfide, diallyl trisulfide, ajoene, and allicin, which have potent antioxidative, antibacterial, antiviral, and anticancer properties. [11][12][13] The major watersoluble sulfur compound, S-allyl-l-cysteine, in garlic extract seems to have direct inhibitory effect on nuclear factor-jB (NF-jB) and indirect inhibitory effect on lipopolysaccharide (LPS)-induced IL-1b and TNF-a in human whole blood. 14,15 The lipid-soluble sulfur compounds allicin and diallyl disulfide also inhibit NF-jB and reduce the expression of inducible nitric oxide (NO) synthase (iNOS) in LPS-stimulated macrophages.…”
Section: Introduction Gmentioning
confidence: 99%
“…[4][5][6][7][8][9] The mechanisms of garlic for its biological activities have been ascribed to its potent antioxidative, 10) antithrombotic 1) and lipid-lowering 11) activities, and to its stimulating ability for immunological responses. 12) Numerous studies have demonstrated that a garlic extract and its related compounds with anti-inflammatory effects inhibited the nuclear factor kappa B (NF-B) activation induced by various receptor agonists, including tumor necrosis factor (TNF) and lipopolysaccharide (LPS), 13,14) and the expression of inducible nitric oxide synthase (iNOS) in activated macrophages. 15,16) NF-B is a central transcription factor for pro-inflammatory gene expression.…”
mentioning
confidence: 99%
“…[14,22] Studies have indicated that garlic oil shows an anti-inflammatory effect by reducing the production of IL2, IL12, IL6, IL8, and TNF-α and by increasing the production of IL10. [23,24] Keiss et al, [25] showed that garlic oil reduced the activation of NFκB and the production of IL1β and TNF-α. Chang et al, [26] found that garlic oil showed anti-inflammatory effects in suppressing the production of nitric oxide (NO) and prostaglandin E2 in activated macrophages.…”
Section: Discussionmentioning
confidence: 99%